Comparative investigation of stimulus-evoked rod outer segment movement and retinal electrophysiological activity - Lu, Yiming (Proc SPIE Int Soc Opt Eng, 2017)
Transient retinal phototropism (TRP) has been observed in rod photoreceptors activated by oblique visible light flashes. Time-lapse confocal microscopy and optical coherence tomography (OCT) revealed rod outer segment (ROS) movements as the physical source of TRP. However, the physiological source of TRP is still not well understood. In this study, concurrent TRP and electroretinogram (ERG) measurements disclosed a remarkably earlier onset time of the ROS movements (≤10 ms) than that (∼38 ms) of the ERG a-wave. Furthermore, low sodium treatment reversibly blocked the photoreceptor ERG a-wave, which is known to reflect hyperpolarization of retinal photoreceptors, but preserved the TRP associated rod OS movements well. Our experimental results and theoretical analysis suggested that the physiological source of TRP might be attributed to early stages of phototransduction, before the hyperpolarization of retinal photoreceptors.